IMPLEMENTASI KEBIJAKAN TRANSAKSI NONTUNAI DI JALAN TOL MELALUI KARTU ELEKTRONIK TOL (E-TOLL) PADA PT. JASAMARGA TOLLROAD OPERATOR RUAS MEDAN-KUALANAMU-TEBING TINGGI - Andani Andani; Sally Marisa Sihombing (Smart Education, 2023)
The non-cash transaction policy on toll roads aims to improve services to toll road users. However, in the implementation process, several problems were found, such as traffic jams due to a lack of balances, machine errors at the toll gate and transactions made in cash. This study uses descriptive research method with a qualitative approach. Data collection techniques are carried out by onterviewing, observing, and recording documents related to the implementation of non-cash transaction policies on toll roads. The data obtained was then analyzed qualitatively by reviewing all data collected and supported by interview results. The results of the study were measured based on the Van Meter and Van Horn Implementation models. In standard indicators and policy targets, the implementation of the policy has not fully complied with the established standards so that the objectives have not been fully realized. Human resources carry out their respective functions and non-human resources in the form of equipment already exist and functioning at all toll gates. Communication between organizations and activity implementers shows that executors routinely coordinate and communicate with other stakeholders. The characteristics of implementing agents show that policy implementers know and understand the policy of non-cash transactions on toll roads. In terms of social, economic and political conditions, it was found that there were many road users whose awareness was still low and road users considered the MKTT toll tariff to be quite expensive. The attitude of the implementer in carrying out the non-cash transaction policy on the toll road is quite responsive when a problem occurs.